3462 Community-Engaged Research in Emergency Dispatch: Getting a 360 View - Alissa L Wheeler; Heather Darata; Jenny Hurst (Journal of Clinical and Translational Science, 2019)
OBJECTIVES/SPECIFIC AIMS: Community-engaged research can provide important input to researchers to understand the impact of health services on diverse communities. In emergency (911) dispatch research, most studies have focused on specific health conditions, especially on identifying and managing those conditions remotely and identifying the most appropriate resources to send. Community-engaged research can add a needed component to these studies, identifying not only what happens when someone calls 911, but who calls and who doesn’t, what barriers community members encounter when they call, and what they expect from their 911 service. METHODS/STUDY POPULATION: A recent study published in the Journal of Clinical and Translational Science outlined a method for identifying and evaluating the needed competencies and readiness of individual researchers to do effective community-engaged research. The investigators involved in an ongoing study on community attitudes toward 911 propose to use the methods outlined in that study to receive feedback from their Community Advisory Board on their own competencies and readiness. RESULTS/ANTICIPATED RESULTS: It is anticipated that 13 people will be involved in providing feedback to the investigators, including all official member of the Community Advisory Boards and all supportive academic staff and faculty. The feedback will be gathered using a survey instrument developed from the recently-published study and will include questions about the purpose of the research, openness to feedback, communication, cultural sensitivity, community presence, power sharing, recognizing partner contributions, and developing community capacity. DISCUSSION/SIGNIFICANCE OF IMPACT: Identifying the most appropriate resources to send to any given emergency is the primary role of the emergency dispatcher. However, they are also public servants, providing care and comfort in a time of stress to members of many diverse communities. As such, it is critical that they understand the needs and expectations of those communities, as well as the barriers they face in calling 911. The proposed study adds value to an ongoing community-engaged research project by providing feedback about readiness and competency to the investigators.